Absolute Time: The Limit of Kant's Idealism. (9th September 2017) - Stan, Marius
Abstract: I examine here if Kant can explain our knowledge of duration by showing that time has metric structure. To do so, I spell out two possible solutions: time's metric could be intrinsic or extrinsic. I argue that Kant's resources are too weak to secure any intrinsic, transcendentally‐based temporal metrics; but he can supply an extrinsic metric, based in a metaphysical fact about matter. I conclude that Transcendental Idealism is incomplete: it cannot account for the durative aspects of experience—or it can do so only with help from a non‐trivial metaphysics of material substance.